LEAN MANUFACTURING APPROACH USING COST INTEGRATED VALUE STREAM MAPPING TO REDUCE WASTE IN FAKE EYELASHES PRODUCTION FLOOR - Prakoso, Indro; Nurjannah, Anisa; Alvianitasari, Dewi; Huaida, Akasa (Center for Study and Journal Management FTI UMI, 2025)
Fake eyelashes are made in Indonesia by a variety of industries. There are issues within the company that have an impact on the output. Waste issues in the manufacture of fake eyelashes are the cause of inconsistent production output, such as flaws in the goods, waiting times, and improper processing. A lean manufacturing approach is required to find a solution to the issues that PT. X is experiencing as a result of the data model. The Value Stream Mapping (VSM) method, the Activity Based Costing (ABC) method integration, the Value Stream Analysis Tools (VALSAT) method calculation, the Root Cause Analysis (RCA) method, and then gives recommendations for improvement. The use of continuous flow, task combinations, and the delivery of raw materials once each week are all suggested improvements. When current cost integrated value stream mapping is compared to future cost integrated value stream mapping, the production lead time drops from 0.5 days to 0.36 days, the total value-added cost drops from 2.049 to 1.561, the total non-value-added cost drops from 12.754 to 11.243, and the travel distance drops from 99 meters to 79 meters.